VALUATION OF THE RIGHT OF HABITATION AND CASE STUDIES (Third Sector Social Economic Review, 2025)
Real estate valuation is essential not only for private sector applications such as insurance and banking but also for public services including expropriation, taxation, privatization, planning, urban transformation, and infrastructure projects. Valuation reports may be requested by various actors in the real estate market and play a crucial role in investment decisions, financial system stability, and strategic planning. Accurate valuation of real estate is particularly critical for purchase and sale transactions, financial reporting, and tax assessments. In Türkiye, existing practices related to the valuation of limited rights in rem are based on flawed foundations and pose certain developmental risks. One such issue concerns the valuation of the right of habitation. This study aims to analyze the impact of the right of habitation, a type of limited real right, on real estate value and to determine the appropriate valuation methodology through examples. To achieve this, a literature review was conducted, and current valuation practices for the right of habitation were examined. The study employs a normative research approach to investigate how this right affects real estate value. Additionally, it provides examples demonstrating the correct calculation methods for the valuation of the right of habitation in accordance with International Valuation Standards (IVS). The study highlights the importance of using the TRH-2010 Life Table in these calculations to ensure accuracy and consistency.
Keywords: Real estate; housing; right of habitation; value of the right of habitation; valuation